Practitioner Perspectives on a Restorative Community: An Inductive Evaluative Study of Conceptual, Pedagogical, and Routine Practice - Thomas Procter-Legg (Laws, 2021)
The purpose of this study is to explore restorative practice (RP) within education, highlighting practitioner views from an inductive evaluative perspective. This is in response to the suggested ambiguity over what constitutes RP in education. Practitioner perspectives are explored, providing an insight into an established restorative school. New data offer further clarity on RP in education by describing embedded practice and highlighting sites for further specific task analysis. Methods include semi-structured questionnaires in the form of employee practice statements, situated within insider research. Eleven practice statements were completed, which were then subject to in-depth thematic analysis. The main findings of this study suggest that RP is clearly understood in this educational setting and participants described a wholistic approach that is part of a wider culture, not just practice as an intervention. Analysis suggests that this can be categorised into the following three themes: Conceptual, Pedagogical and Routine Practice. When used alongside one another, it is suggested that these themes create a restorative paradigm, which is of relevance to the field of education. As such, this paper is designed to provide a useful resource for schools, policy makers and researchers alike.